2010
DOI: 10.1007/s10995-010-0621-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Low Birth Weight Among Newborns of Early Adolescents, Late Adolescents, and Adult Mothers in the Peruvian Amazon

Abstract: To compare low birth weight (LBW: <2,500 g) between infants born to adolescent and adult mothers in Iquitos, Peru. A random sample of 4,467 records of women who delivered at the Hospital Apoyo Iquitos between 2005 and 2007 was collected from hospital birth registries. Multivariate logistic and linear regression analyses were performed to compare LBW in newborns of adolescents (10-14, 15-19 years) and adults (≥20 years) and then for primiparous mothers with a normal gestational age, adjusting for newborn sex, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
6
0
2
Order By: Relevance
“…Maternal age was found significantly associated with low birth weight infants. The younger age group is at risk of having LBW babies compared to older age group and this finding is consistent with other studies [10] [13] [22]- [24]. However, there were also studies reported that the older maternal age is at higher risk in getting LBW infants [16].…”
Section: Discussionsupporting
confidence: 90%
“…Maternal age was found significantly associated with low birth weight infants. The younger age group is at risk of having LBW babies compared to older age group and this finding is consistent with other studies [10] [13] [22]- [24]. However, there were also studies reported that the older maternal age is at higher risk in getting LBW infants [16].…”
Section: Discussionsupporting
confidence: 90%
“…El embarazo adolescente puede mostrar variación en su relación con las complicaciones obstétricas y perinatales no solo por un aspecto relacionado con la madurez biológica, sino también por factores sociales y culturales que no hemos medido, como las condiciones socioeconómicas, el acceso a la educación y servicios de salud, relaciones familiares, condiciones de pareja y estabilidad emocional, que son diferentes entre adolescentes y adultas y que están asociados a algunas complicaciones que hemos evaluado. 28,29 Es por esto que es importante conocer los riesgos diferenciados por lugares, pues estos otros factores no medidos, pueden contribuir a un perfil distinto de los riesgos del embarazo adolescente en cada región.…”
Section: Discussionunclassified
“…In the literature, regardless of whether adolescent pregnant women are in underdeveloped, developing, or developed countries, their babies' weight is lower than that of adult pregnant women. [16][17][18][19][20][21][22] Gestational age was also lower in the adolescent pregnant group compared to the adult cohorts. It is understood that this situation is associated with preterm birth and IUGR.…”
Section: Discussionmentioning
confidence: 91%